A 1, 4-benzoquinone derivative isolated from Ardisia crispa (Thunb.) A. DC. root suppresses angiogenesis via its angiogenic signaling cascades - Lim, Wen Jun; Chan, Pit Foong; Hamid, Roslida Abd (Elsevier B.V., 2024)
The root hexane extract of Ardisia crispa (ACRH), which belongs to the Primulaceae family, has been reported to possess anti-inflammatory, chemopreventive, anti-arthritic, and antiangiogenic activities. In this study, we isolated a p-benzoquinone derivative, 2-methoxy-6-undecyl-1,4-benzoquinone (AC2), from ACRH and investigated its potential antiangiogenic activity in human umbilical vein endothelial cells (HUVECs) and zebrafish embryo models. Prior to this study, AC2 was characterized using 1H NMR spectroscopy and MS. AC2 significantly suppressed HUVEC proliferation in a time-independent manner, with an IC50 value of 1.35 ± 0.05, 1.15 ± 0.02, and 1.00 ± 0.01 µg/mL at 24, 48, and 72 h, respectively. AC2 also induced apoptosis in HUVECs and significantly suppressed their migration, invasion, and tube formation in a concentration-dependent manner. Additionally, AC2 significantly attenuated most of the analyzed protein markers, including pro-MMP-2, VEGF-C, VEGF-D, angiopoietin-2, endothelin-1, fibroblast growth factor (FGF)-1, FGF-2, follistatin, heparin-binding epidermal growth factor-like growth factor (HB-EGF), and hepatocyte growth factor (HGF) at all tested concentrations. Furthermore, AC2 significantly inhibited zebrafish embryo intersegmental vessels (ISVs), confirming its antiangiogenic role. In conclusion, AC2 exhibits a potential anti-angiogenic effect by suppressing several proangiogenic and growth factors. Further studies are needed to investigate their effects on other excessive angiogenic diseases.